Sociology with Christianity: The Last Attempt of Charles A. Ellwood to Right the Wrong - LoConto, David G. (Journal for the sociological integration of religion and society, 2014)
Charles A. Ellwood, one of the first doctorates in Sociology in the United States, and the father of Sociological Social Psychology published several articles and books on the purpose of the discipline. In addition to extending John Dewey's Functional Psychology, he focused on the idea of qualitative methods as a scientific method. The integration of Christianity with sociology has largely been ignored in his work. The following addresses his ideas on this integration. He addressed five key areas that occurred in the United States as people became more secular: (1) the reliance on theology; (2) the development and institutionalization of a sensate culture; (3) the ignorance of science toward the metaphysical; (4) the Christian position on war; and (5) business as selfishness. He advocated turning to the words of Christ and thereby (1) creating an absolute from which right and wrong were discernible; (2) that the words of Christ connect with natural law and collectivity; and (3) that Jesus stipulated the interconnectedness of everything, therefore resulting in the responsibility for all. His hope was that by abiding by the words of Christ that people would work collectively to help each other.